The Relationship Between Trading Volume، Stock Returns and Volatility in the Saudi Stock Market - Rohat Sheikh Esmaeel Zada (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The aim of this study is to investigate the relationship between trading volume، on one hand، and stock returns and volatility on the other، in the financial stock market. In this respect، we employ the study on all companies listed on the Saudi Stock Market in January 1، 2005. Accordingly، this is the start of the sample. Primarily، the study is based on two assumptions. We consider 69 companies out of 73 ones for the first assumption. The statistical analysis is conducted using Eviews Package and Ms Excel. The empirical evidence by OLS regression analysis indicated that there exists a significant positive relationship between trading volume and stock return، and their volatility. Furthermore، Granger causality results showed evidence of causation between trading volume and stock return. The results of Vector Autoregression (VAR) ، on the one hand، provided evidence of dynamic relationship between trading volume and stock return. The empirical evidence of GARCH model indicated the existence of positive contemporaneous relationship between trading volume and stock return conditional volatility. The findings showed that the relationship between trading volume and stock return is rejected by MDH، thereby indicating that the Saudi Stock Market is not semi-strong efficient.